2020
DOI: 10.3389/fped.2020.00179
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Necrotizing Enterocolitis in Infants With Patent Arterial Duct. A Retrospective Matched Paired Analysis

Abstract: Background: The development of necrotizing enterocolitis (NEC) in neonates with patent ductus arteriosus (PDA) is not well-understood. Our aim was to find risk factors for NEC in children with a significant PDA and to assess differences in mortality and duration of hospital stay between patients with PDA and those with PDA and NEC. Methods: We performed a retrospective single center case control study including infants with PDA scheduled for treatment. We compared multiple patient data between patients with PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…There was no association between infants who developed one episode of isolated hypotension during the first 72 hours of life and NEC, irrespective of whether they were treated for hypotension or not, in a subgroup of EPIPAGE 2 cohort study 28 . In a retrospective case control study, Haefeli et al reported that hypotension did not increase the risk of NEC in infants with PDA 29 . Similar to the present study, Faust and colleagues reported that severe NEC was lower among babies with high BP compared to babies with low BP during the first 24 hours of life 3 .…”
Section: Discussionmentioning
confidence: 97%
“…There was no association between infants who developed one episode of isolated hypotension during the first 72 hours of life and NEC, irrespective of whether they were treated for hypotension or not, in a subgroup of EPIPAGE 2 cohort study 28 . In a retrospective case control study, Haefeli et al reported that hypotension did not increase the risk of NEC in infants with PDA 29 . Similar to the present study, Faust and colleagues reported that severe NEC was lower among babies with high BP compared to babies with low BP during the first 24 hours of life 3 .…”
Section: Discussionmentioning
confidence: 97%
“…The pathophysiology of NEC is multifactorial and has not as of yet been fully clarified. Prematurity, formula feeding, and intestinal dysbiosis are the main risk factors, while the genetic predisposition as well as certain prenatal and postnatal factors increase the risk of NEC ( Table 1) (12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Pathophysiology and Current Diagnosis Of Necrotizing Enterocmentioning
confidence: 99%